Chemokine (C-X-C motif) ligand 1 is associated with tumor progression and poor prognosis in patients with colorectal cancer. Issue 4 (3rd July 2018) - Zhuo, Changhua; Wu, Xianyi; Li, Jing; Hu, Dan; Jian, Jinliang; Chen, Changjiang; Zheng, Xiongwei; Yang, Chunkang
Abstract : Chemokine (C-X-C motif) ligand 1 (CXCL1) is a chemotactic cytokine known to regulate cancer progression and invasion. However, the prognostic significance of CXCL1 expression in colorectal cancer (CRC) has not been fully characterized. The present study explored the clinicopathological significance and potential role of CXCL1 in the carcinogenesis and progression of CRC. The protein expression of CXCL1 was measured immunohistochemically in tissue microarrays constructed from 276 CRC patients. CXCL1 expression levels and their associations with clinicopathological characteristics and patient survival were evaluated. The effect of CXCL1 on glycolysis was also examined . High CXCL1 expression was detected in 165 (59.8%) cases. CXCL1 expression was correlated with tumor diameter ( P =0.002), T stage ( P =0.044), N stage ( P =0.005), M stage ( P =0.001), lymphovascular invasion ( P =0.010), and carcinoembryonic antigen status ( P =0.019). High CXCL1 expression was validated as an independent prognostic factor for overall survival (OS) and disease-free survival (DFS) by both univariate and multivariate Cox regression analyses (both P <0.05). Experimentally, expression of CXCL1 was knocked down by stable transfected short hairpin RNA, resulting in a significantly decreased rate of glycolysis both in in vitro assays and in patients' samples ( P <0.05). Silencing the expression of CXCL1 decreased the levels of the glycolytic enzymes GLUT1, HK2, and LDHA. In conclusion, by inducing glycolysis, CXCL1 plays a crucial role in both cancer progression and metastasis in CRC patients. The CXCL1 expression level is an independent prognostic factor for both OS and DFS. Moreover, CXCL1 may serve as a new biomarker and potential therapeutic target for CRC treatment.